Peculiarities of master’s teacher training in distance education in Turkey - Postryhach, N. (New Collegium, 2023)
The reform of higher education assumes a transition to the preparation of masters in education by introducing modern approaches to mastering innovative technologies of mass education, taking into account world experience and meeting the needs for self-learning and self-improvement throughout life. In turn, distance education every year more and more actively influences the classical forms of education, enriching traditional education with innovative content and organizational components. Comparative studies testify that distance learning can be as effective as classroom learning, if the methods and technologies meet the tasks, there is interaction between students, and there is timely feedback between the teacher and the student. Successful distance learning programs are based on consistent and comprehensive efforts of students, teachers, coordinators, support staff and administration. As a result of the analysis of foreign experience, it was revealed that the introduction of mass open distance courses as a form of education requires further improvement of their organization and curriculum. It is outlined that for the implementation of such courses in the process of master's teacher training, the content of educational and scientific programs and educational and professional characteristics of the future specialist should be observed; mass open distance courses must be included in the curriculum, where the number of hours and credits for studying the relevant discipline is clearly indicated; curricula must be improved by introducing a new form of education. Distance education offers prospective and practicing teachers both skills training and the opportunity to complete teacher training programs or obtain a degree. The distribution of distance teacher training programs is not limited to developed or developing countries, nor to specific delivery methods. This proliferation is the result of the rapid development of telecommunications technologies combined with a growing awareness of ways to use technology for teacher training. Thus the content analysis of the professional literature on the problem of scientific research made it possible to identify and summarize the pecularities of masters teacher training in distance education in Turkey: the use of active and mass learning methods; methods for assessing the progress of applicants for higher education, methods of mass self-education, introspection and self-correction of knowledge; conducting courses through videoconferencing, virtual classes and forums with synchronous interaction between students and teachers; communication through forums, online conversations and online interviews; use of various printed, visual, classroom and electronic materials. The predictive potential of scientific research is due to the potential possibility of further scientific research on the problem of the curriculum developing of master’s teacher training in distance education in Turkey.